Technology and the Historian : Transformations in the Digital Age - Crymble, Adam (Book collections on Project MUSE., 2021)
"Historians have seen their field transformed by the digital age. Research agendas, teaching and learning, scholarly communication, the nature of the archive-all have undergone a sea change that in and of itself constitutes a fascinating digital history. Yet technology's role in the field's development remains a glaring blind spot among digital scholars. Adam Crymble mines private and web archives, social media, and oral histories to show how technology and historians have come together. Using case studies, Crymble merges histories and philosophies of the field, separating issues relevant to historians from activities in the broader digital humanities movement. Key themes include the origin myths of digital historical research; a history of mass digitization of sources; how technology influenced changes in the curriculum; a portrait of the self-learning system that trains historians and the problems with that system; how blogs became a part of outreach and academic writing; and a roadmap for the continuing study of history in the digital era"--